Sistem Pemantauan Literasi Pelajar Tahap 1 - Hassan, Norlida; Abdul Rahim, Hanisah Husna (Applied Information Technology And Computer Science, 2020)
Abstract: Sistem Pemantauan Litersi Pelajar Tahap 1 is a web-based system that works to help teachers monitor level 1 students’ literacy. Currently, the process of monitoring student literacy is done manually and many parents are unaware that this process of monitoring is taking place in all schools. The existing system will increase the workload of teachers in the process of updating student literacy assessment. In addition, with information obtained from teacher monitoring, reports will be generated for documentation purposes on behalf of the school. Therefore, new systems need to be developed to help teachers solve the data management problems they face. Therefore, Sistem Pemantauan Litersi Pelajar Tahap 1 was developed to help teachers keep students’ information organized and parents can engage in the process of building student literacy skills. Parents can also monitor the increase in students’ literacy without having to attend self-study sessions with teachers. The prototype model is used as a methodology to develop this system. Software used in the development of this system is Adobe Dreamweaver, and Node.Js. Through this system, it will help the teacher to record the increase in students’ literacy and parents can see the assessment given by the teacher. The production of reports can also help teachers in improving student mastery of construction. The report will also be able to show the level of mastery of the building that needs to be mastered. Abstrak: Sistem Pemantauan Literasi Pelajar Tahap 1 merupakan satu sistem yang berasakan web yang berfungsi untuk membantu guru memantau penguasaan literasi pelajar tahap 1. Pada masa sekarang, proses pemantauan literasi pelajar dilakukan secara manual dan ramai ibu bapa tidak mengetahui akan perlaksanaan proses pemantauan ini berlaku di semua sekolah. Oleh itu, Sistem Pemantauan Literasi Pelajar Tahap 1 dibangunkan untuk membantu guru untuk menyimpan maklumat pelajar dengan lebih teratur dan ibu bapa dapat melibatkan diri dalam proses membina kemahiran literasi pelajar. Model prototaip digunakan sebagai metodologi untuk membangunkan sistem ini. Perisian yang digunakan dalam pembangunan sistem ini adalah Adobe Dreamweaver, dan Node.Js. Melalui sistem ini, ia akan dapat membantu guru dalam merekod peningkatan dalam penguasaan literasi pelajar dan ibu bapa dapat melihat penilaian yang diberikan oleh guru tersebut.